2012
DOI: 10.1007/s13402-012-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

EGFR and KRAS mutations in lung carcinomas in the Dutch population: increased EGFR mutation frequency in malignant pleural effusion of lung adenocarcinoma

Abstract: BackgroundFrequencies of EGFR and KRAS mutations in non-small cell lung cancer (NSCLC) have predominantly been determined in East Asian and North American populations, showing large differences between these populations. The aim of the present study was to determine the frequency of EGFR and KRAS mutations in NSCLC in the West European Dutch population in primary carcinomas and different metastatic locations.MethodsEGFR (exons 19, 20 and 21) and KRAS (exons 2 and 3) mutation test results of NSCLC samples of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
64
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 31 publications
(63 reference statements)
16
64
3
4
Order By: Relevance
“…In lung adenocarcinoma, KRAS mutations are more common in smokers (12)(13)(14)(15)(16). The prognostic significance of KRAS mutations in NSCLC is controversial (17)(18)(19). Maitra et al (20) identified KRAS mutations in 2 (17%) of 12 gallbladder EPSCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung adenocarcinoma, KRAS mutations are more common in smokers (12)(13)(14)(15)(16). The prognostic significance of KRAS mutations in NSCLC is controversial (17)(18)(19). Maitra et al (20) identified KRAS mutations in 2 (17%) of 12 gallbladder EPSCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 6 (16.2%) of 37 SCLC patients had KRAS mutations. There were ethnic and geographical differences in the KRAS mutation status of patients with colorectal cancer and NSCLC (19,23,24). Genetic, dietary and environmental factors play a role in the development of KRAS mutations.…”
Section: Discussionmentioning
confidence: 99%
“…A typical tumor contains two to eight driver mutations that can affect as many as 12 key cellular signaling pathways. Reported genetic alterations for lung adenocarcinoma include: EGFR (32,(42)(43)(44)(45)(46)(47), KRAS (42,(48)(49)(50)(51)(52), BRAF (53)(54)(55)(56), and ERBB2 (formerly HER2) (45, 56-60) driver mutations; ROS1 (32,(61)(62)(63), KIF5b-RET (32,64,65), and EML4-ALK rearrangements (20,45,57,61,(66)(67)(68)(69)(70); and other gene amplifications (20). An estimated 50% of lung adenocarcinomas in patients in Western populations have either an EGFR or KRAS driver mutation (42).…”
Section: Clinical Issuesmentioning
confidence: 99%
“…An estimated 50% of lung adenocarcinomas in patients in Western populations have either an EGFR or KRAS driver mutation (42). The two mutations are mutually exclusive (52). In approximately 30-40% of patients with adeno-carcinoma a driver mutation has not been identified (20), which leaves substantial room for the development of additional targeted treatments for these tumors.…”
Section: Clinical Issuesmentioning
confidence: 99%
See 1 more Smart Citation